Plans for front yard planting - Kirkwood, Nina H. (My University, 1905)
Introduction: The term “landscape gardening” usually gives an impression of something large and expansive but in its true meaning it does include the decoration of the home lot. Everyone should at least understand the aim of landscape gardening as applied to the home as this is where most of our interests center. Very little of this decorative planting can be done in the city but aside from homes inside of the city limits it may be accomplished by a little study. The home should always be built so that it will fit the landscape that it so it will look as if it belonged there and the decoration of the guard should do the same and if we consider it as a part of the landscape the decoration of it will then clearly come under the subject of “Landscape Gardening”. Even in the homes in small towns and suburban homes by the cooperation of the owners the landscape gardening may be made very effective there. Before beginning to work on the lot no matter how small one should always have a plan made first.
Citation: Kirkwood, Nina H. Plans for front yard planting. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Make Plan Before Planting; Investigating Building Sites; Theses; Manuscripts (documents)